Intercultural Christology in John's Gospel : a Subaltern Reading from India - Chacko, Biju [Author] (Meneapolis : Fortress Press, 2022)
This book unravels the intercultural intersections and subaltern dimensions of John's Christology. The Johannine Messiah is a subaltern Messiah, and the Johannine community is subaltern community. The evangelist resists and disrupts, even while resonating with the surrounding linguistic and conceptual milieu. Therefore, a hermeneutical framework of intercultural resonance and subaltern subversive rhetoric is a key to unlock St. John's Gospel. This book follows such a hermeneutical approach.
Keywords: Gospel of John; Subaltern Studies